Strategi Pencegahan Perilaku Self-Harm pada Remaja - Nurmala Sari Wicaksono; Wanodya Kusumastuti; Widyaning Hapsari (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
Self-harm behavior in adolescents is a form of escape from emotional pressure, stress, and feelings of helplessness experienced in the process of psychosocial development. This study aims to identify effective prevention strategies in suppressing self-harm behaviors in adolescents. The research method used was a qualitative approach with an in-depth interview technique with four adolescents aged 13–20 years who had experience related to self-harm behavior and one supporting informant who had handled self-harm cases. The data were analyzed using a thematic approach to find patterns of coping strategies used by adolescents in dealing with psychological distress. The results of the study show that effective prevention strategies include increased social support from family and peers, mental health education in schools, and ongoing counseling assistance. In addition, strengthening emotion regulation skills and self-awareness is an important factor in reducing the risk of self-harm. The findings of this study confirm the importance of the role of the immediate environment in creating a sense of security and acceptance for adolescents. Therefore, collaboration between families, schools, and mental health professionals is needed to build a comprehensive and sustainable prevention system.